Work Environment-Related Risk Factors for Leptospirosis among Plantation Workers in Tropical Countries: Evidence from Malaysia - Ridzuan, J Mohd; Daud, Aziah; Zahiruddin, WM (National Iranian Oil Company (NIOC) Health Organization, 2016)
Background: Leptospirosis is a zoonotic disease that is recognized as a re-emerging global public health issue, especially in tropical and subtropical countries. Malaysia, for example, has increasingly registered leptospirosis cases, outbreaks, and fatalities over the past decade. One of the major industries in the country is the palm oil sector, which employs numerous agricultural workers. These laborers are at a particularly high risk of contracting the disease. Objective: To identify the work environment-related risk factors for leptospirosis infection among oil palm plantation workers in Malaysia. Methods: A cross-sectional study involving 350 workers was conducted. The participants were interviewed and administered a microscopic agglutination test. Seropositivity was determined using a cut-off titer of ≥1:100. Results: 100 of 350 workers tested positive for leptospiral antibodies, hence, a seroprevalence of 28.6% (95% CI 23.8% to 33.3%). The workplace environment-related risk factors significantly associated with seropositive leptospirosis were the presence of cows in plantations (adjusted OR 4.78, 95% CI 2.76 to 8.26) and the presence of a landfill in plantations (adjusted OR 2.04, 95% CI 1.22 to 3.40). Conclusion: Preventing leptospirosis incidence among oil palm plantation workers necessitates changes in policy on work environments. Identifying modifiable factors may also contribute to the reduction of the infection.